Differences in the Relationship Between Family Environments and Self-Determination Among Anglo, Latino, and Female Students With Disabilities. (December 2013) - Rodriguez, Raymond J.; Cavendish, Wendy
The role of gender and ethnicity as moderators of the relationship between perceived family environments and levels of self-determination was examined in a sample of students with disabilities. A sample of 157 Latino and Anglo students with disabilities completed the Family Environment Scale and the Arc Self-Determination Scale . Results indicated Latino and female students reported significantly higher levels of self-determination than Anglo male students. Differences were also found among Latino, Anglo, and female students in the relationship between perceived family environments and self-determination. Implications include developing ways families and schools can provide conditions to nurture self-determination and transition planning that are sensitive to ethnic and gender differences.